Reduced energy resources in pork production - Uskenov, R. B.; Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна (ТДАТУ, 2020)
One of the largest consumers of energy in Ukraine is the agricultural sector. Therefore, from the point of view of the strategy of sustainable development and rational use of material and energy resources and energy efficiency of the agrarian sector of Ukraine, in particular the livestock industry, it is necessary to undertake the economic rationale of the strategy of Energogarant and develop modern scientific and normative framework for the design of energy efficient livestock facilities to carry out the modernization of existing buildings, to bring the Ukrainian agricultural market modern and innovative system of construction; technologies and materials; to determine the direction of the possible use of nonconventional renewable energy sources in the livestock industry
Keywords: the agricultural sector; energy sources in the livestock industry; innovative system; livestock products; blower heat generators